Effects of Lacticaseibacillus casei (Lactobacillus casei) and Saccharomyces cerevisiae mixture on growth performance, hematological parameters, immunological responses, and intestinal microbiome in weaned pigs - Kim, Sheena; Kwak, Jinok; Song, Minho; Cho, Jinho; Kim, Eun Sol; Keum, Gi Beom; Doo, Hyunok; Pandey, Sriniwas; Cho, Jae Hyoung; Ryu, Sumin; Kim, San; Im, Yu-Mi; et al. (Frontiers in Veterinary Science, 2023)
This study was conducted to evaluate the effects of Lacticaseibacillus casei (Lactobacillus casei) and Saccharomyces cerevisiae mixture on growth performance, hematological parameters, immunological responses, and gut microbiome in weaned pigs. A total of 300 crossbred pigs ((Landrace × Yorkshire) × Duroc; 8.87 ± 0.34 kg of average initial body weight [BW]; 4 weeks of age) were divided into two dietary treatments (15 pigs/pen, 10 replicates/treatment) using a randomized complete block design (block = BW): control (CON) and the effective microorganism (MEM). The CON was not treated, while the MEM was treated with the mixture of L. casei (1 x 107 CFU/mL) and S. cerevisiae (1 x 107 CFU/mL) at 3 mL/pig/day for 4 weeks via the drinking water supply. Two feces and one blood sample from the randomly selected pigs in each pen were collected on D1 and D28 after weaning. Pigs were individually weighed, and pen feed intakes were recorded to evaluate pig growth performance. For the gut microbiome analysis, 16S rRNA gene hypervariable regions (V5 to V6) were sequenced using the Illumina MiSeq platform, and Quantitative Insight into Microbial Ecology (QIIME) and Microbiome Helper pipeline were used for 16S rRNA gene sequence analysis. The daily weight gain and feed efficiency of MEM were significantly higher than those of CON (P < 0.001). There were no significant differences in hematological parameters and immune responses between CON and MEM. However, MEM had significantly lower Treponema genus, whereas significantly higher Lactobacillus and Roseburia genera compared to CON. Overall, our data showed that L. casei and S. cerevisiae mixture could promote growth performance through the modulation of gut microbiota in pigs. This study will help to understand the correlation between the growth performance and the gut microbiome.